Bannayan-Riley-Ruvalcaba Syndrome, Rare Etiology of Intestinal Hamartomatouspolyposis: A case report (Bangladesh Journal of Child Health, 2019)
Bannayan-Riley-Ruvalcaba syndrome (BRRS) is a rare autosomal dominant congenital disorder, characterized bymacrocephaly, lipomas, hamartomas, and pigmented macule in genitalia.Several dozen cases have been reported in the medical literature, but no case has been reported in Bangladesh. We report a case of BRRS in a 11-year-old male child with recurrent per rectal bleeding with hamartomatouscolonic polyposis & multiple subcutaneous lipomas on the anterior abdominal wall.In addition, patient had macrocephaly, intellectual impairment.Bleeding polyps were removed by colonoscopic polypectomy.Bangladesh J Child Health 2019; VOL 43 (1) :62-65